Vidurio Rytų Europa XX amžiaus antrosios pusės lenkų išeivijos federalistinėse regioninėse koncepcijose - Stankevič, Barbara (Lietuvos istorijos studijos, 2011)
The most prominent representatives of the federalist concept among Polish emigrants of the second half of the 20th century are considered to be historian Oskar Halecki (1891-1973) and editor/politician Jerzy Giedroyc (1906-2000). They made a tremendous influence on the Polish historiographical and geopolitical thought. The present article is dedicated to their activities and has formulated the concepts meant for the substantiation of the federal past of East Central Europe and the independence of the region.The developments of World War II and post-war periods conditioned a half-century-long dualistic division of Europe into the democratic West and the Communist East, which left a deep imprint in the world historiography. Disagreeing with the dualistic representation of Europe, O. Halecki suggested his own concept; he summarized the discussions of historians and politicians of the first half of the 20th century concerning such concepts as Eastern Europe, Slavic Europe, Central or East Central Europe. This was reflected in his publication "The Limits and Divisions of European History". In it, he suggested dividing Europe not into two or three but into four parts - Western, Eastern, West Central, and East Central.The concept of Europe which he had formulated was further expanded not only by the main centres of political thought of the USA, but also by Polish emigrants, and among them by the Institute of Literature which was situated in France, near Paris, in the Maisons-Laffitte suburb and was headed by Jerzy Giedroyc. The journals "Culture" and "Notebooks of History", edited by Giedroyc, presented the concept of ULB (to name the former lands of the Grand Duchy of Lithuania - Ukraine, Lithuania, Belarus) and the geopolitical programme of the peaceful co-existence of Poland with its Eastern neighbours in the "subregion" of East Central Europe. This programme distinguished Maisons-Laffitte from the Polish emigrants as immediately after the war it was believed that after the year 1939 and the Yalta agreements changes in the Polish political thought were necessary - the Polish had to give up the claims to Vilnius and Lvov. Under the present circumstances, the ULB concept was seeking to renew the "idea of the Jogaila dynasty", which was popular in the post-war period, by dialectically criticizing it and discarding its imperialist form.O. Halecki introduced the homogenic region of East Central Europe into the historiographical discourse and encouraged discussions on its past and future, while J. Giedroyc's geopolitical concept of the ULB subregion contributed to the substantiation of the claims of historical subjects to the cultural/historical regions formulating their identity and encouraged a new cooperation of the countries. Their concepts conditioned changes in the Polish thought and presented new arguments for the formation of a narrative between the former Republic of Both Nations.